Mechanical regulation of breast cancer migration and apoptosis via direct and indirect osteocyte signaling. Issue 7 (14th March 2018) - Ma, Yu‐Heng V.; Lam, Candy; Dalmia, Shreyash; Gao, Peter; Young, Jacob; Middleton, Kevin; Liu, Chao; Xu, Henry; You, Lidan
Abstract: Bone metastases, the migration of cancers to bone, occur in 65‐80% of patients with advanced breast cancer. Metastasized cancer cells interact with cells such as the bone‐resorbing osteoclasts to alter bone remodeling. Exercise, often suggested as an intervention for cancer patients, regulates bone remodeling via osteocytes. Osteocytes also signal to endothelial cells, which may affect cancer cell extravasation. Therefore, we hypothesize that mechanically stimulated osteocytes can regulate processes in breast cancer bone metastasis. To test this, we exposed osteocytes to oscillatory fluid flow in vitro using parallel‐plate flow chambers. We observed that conditioned medium from flow‐stimulated osteocytes increased migration (by 45%) and reduced apoptosis (by 12%) of breast cancer cells. Conditioned medium from osteoclasts conditioned in flowed osteocytes' conditioned medium reduced migration (by 47%) and increased apoptosis (by 55%) of cancer cells. Cancer cell trans‐endothelial migration was reduced by 34% toward flowed osteocytes' conditioned medium. This difference was abolished with ICAM‐1 or IL‐6 neutralizing antibodies. Conditioned medium from endothelial cells conditioned in flowed osteocytes' conditioned medium increased cancer cell apoptosis by 29%. To summarize, this study demonstrated mechanically stimulated osteocytes' potential to affect breast cancer cells not only through direct signaling, but also through osteoclasts and endothelial cells. The anti‐metastatic potential of the indirect signalings is particularly exciting since osteocytes are further away from metastasizing cancer cells than osteoclasts and endothelial cells. Future studies into the effect of bone mechanical loading on metastases and its mechanism will assist in designing cancer intervention programs that lowers the risk for bone metastases. Abstract : Applying conditioned medium from flow‐stimulated osteocytes directly to breast cancer cells increased their migration and reduced apoptosis. However, incorporating osteoclasts and endothelial cells suggests an anti‐metastatic potential of flow‐stimulated osteocytes, by reducing breast cancer cell migration and extravasation, while increasing their apoptosis.